HH e YHWH: Hilda Hilst e o deus javista - Amorim, Bernardo Nascimento (2007)
In this brief article, I try to juxtapose Hilda Hilst’s poetry and the Hebrew Bible. In order to do that, from a comparative perspective, I concentrate on two fi gures: Tanach’s god and a very singular character present in Hilst’s poems.